2018
DOI: 10.1515/opar-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

How Do We Explain ‛Autistic Traits’ in European Upper Palaeolithic Art?

Abstract: Traits in Upper Palaeolithic art which are also seen in the work of talented artists with autism, including most obviously an exceptional realism, remain to be explained. However any association between the famously evocative animal depictions created in the European Upper Palaeolithic and what is commonly seen as a 'disorder' has always been contentious. Debate over these similarities has been heated, with explanations ranging from famous works of Upper Palaeolithic art having been created by individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 108 publications
0
11
0
Order By: Relevance
“…Similarly, autism shares some of the genetic basis of intelligence, which can explain the relation of the autistic phenotype with the improvement in cognitive performance and convergent thinking, which are essential to creativity ( Crespi, 2016 ). In addition, there may be some relationship between autism, creativity, and artisticality ( Kellman, 1998 ; Spikins et al, 2018 ).…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, autism shares some of the genetic basis of intelligence, which can explain the relation of the autistic phenotype with the improvement in cognitive performance and convergent thinking, which are essential to creativity ( Crespi, 2016 ). In addition, there may be some relationship between autism, creativity, and artisticality ( Kellman, 1998 ; Spikins et al, 2018 ).…”
Section: Mechanismsmentioning
confidence: 99%
“…According to Del Giudice et al (2010) , the prevalence of autism is currently linked to the selection of genes that are associated with greater systematization, greater attention to detail, and the ability to innovate in technical fields, which may have become more helpful from the Holocene, a period characterized by agriculture ( Harpending and Cochran, 2002 ). However, attention to detail is also crucial in archeological cave paintings ( Kellman, 1998 ; Spikins et al, 2018 ). These psychological skills would be worth greater prestige and access to resources in these cultural contexts, also leading to a higher number of mating opportunities for individuals with these skills, particularly men ( Henrich and Gil-White, 2001 ; Del Giudice et al, 2010 ).…”
Section: Functionmentioning
confidence: 99%
“…Resource-scarce environments characteristic of certain phases of human evolution (Potts et al, 2018) are likely to exert a particularly strong selection pressure for more efficient local cognitive search, as supported by research in patch exploitation theory (Stephens et al, 2012). It has also been proposed that autistic traits, namely a local processing bias, were selected for in such contexts (Spikins et al, 2018). This kind of enhanced depth-first search orientation may play an important role in expanding the band-width of cultural inheritance and increasing capacity for adaptation.…”
Section: Implications For Research On Other Neurodevelopmental Disordersmentioning
confidence: 99%
“…More specifically, this paper aims to initiate a re-analysis of objects of European Celtic Art with a "different" eye to ask for the potential of artists with autistic spectrum conditions within its idiom -as has been argued for Palaeolithic cave art (Spikins 2009, 193-5;Spikins and Wright 2016;Spikins et al 2018). By opening a new layer of seeing, my enquiry wishes to approach new visual qualities of the art as well as understanding the visual talents of the ancient designers.…”
Section: Asking New Questions About European Celtic Artmentioning
confidence: 99%
“…On the other hand, research by Penny Spikins and her collaborators has shown that there is potential for neuro-atypical elements within prehistoric art (Spikins 2009;Spikins and Wright 2016). Within autistic spectrum conditions, occasional talent appears of extremely naturalistic drawing skills (Humphreys 1998;Spikins et al 2018). While European Celtic Art is anything but naturalistic, the drawing behaviour pattern of these exceptionally artistic children with ASC creates layers of crowded imagery in which one feature develops into another and in which different, unrelated elements can be fused into new ones.…”
Section: Autistic Spectrum Conditions In European Celtic Art?mentioning
confidence: 99%